2018
DOI: 10.2500/aap.2018.39.4098
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of beef allergy in schoolchildren in Turkey

Abstract: The presence of a family history of beef allergy, beef specific IgE value, and skin test result positivity are independently associated with positive DBPCFC results, and combined evaluation of these three parameters increased the positive predictive power of the tests.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
20
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(22 citation statements)
references
References 0 publications
1
20
1
Order By: Relevance
“…The OFC was prepared in line with current challenge protocols. 12,16 The titrated dose was given separately for beef and mutton as 1, 2, 7, 15, 25, 50 g with 20 min intervals. It was completed as not to exceed 100 g. The patients were monitored for at least 6 hours after the OFC.…”
Section: Oral Food Challengesmentioning
confidence: 99%
See 2 more Smart Citations
“…The OFC was prepared in line with current challenge protocols. 12,16 The titrated dose was given separately for beef and mutton as 1, 2, 7, 15, 25, 50 g with 20 min intervals. It was completed as not to exceed 100 g. The patients were monitored for at least 6 hours after the OFC.…”
Section: Oral Food Challengesmentioning
confidence: 99%
“…Red meat allergy is reported more frequently in the Black Sea region of Turkey. 12,[14][15][16] In a single-center study on the prevalence of red meat allergy in children in the black sea region, the primary beef allergy prevalence was reported to be 0.3%, based on the oral food challenge (OFC) test. 16 In a multicenter study in Turkey, it has been reported that beef is the second food responsible for anaphylaxis in children after milk.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A similarly designed study of 689 adults in Pakistan demonstrated beef allergy in 0.9% of the subjects, a number that exceeded those with allergies to peanut, fish, soy and milk [9]. A recent report of 6000 schoolchildren in eastern Turkey found that 2.6% had symptoms consistent with IgE-mediated beef allergy based on parental report [10]. The number of subjects with confirmed beef allergy upon oral meat challenges was lower at 0.3%, but only a small fraction of those with suspected allergy, and none who reported delayed beef allergy symptoms, consented to the challenges.…”
Section: Introductionmentioning
confidence: 98%
“…In the first report, Kılıç Topçu et al 9 presented their evaluation of the prevalence and characteristics of IgE-mediated beef allergy in urban schoolchildren. They reported that the presence of family history, serum IgE levels to beef, and skin test positivity were independently associated with positive, double-blind, placebo controlled challenge results.…”
mentioning
confidence: 99%